SPERIMENTASI MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER (NHT) DAN STRUCTURED NUMBERED HEADS (SNH) DENGAN PENDEKATAN SAINTIFIK PADA MATERI HIMPUNAN DITINJAU DARI SELF-EFFICACY - Maratu Shalikhah; Budi Usodo; Sri Subanti (Jurnal Pembelajaran Matematika, 2016)
Abstract: The aim of the research was to determine the effect of learning models on mathematics achievement and learning interest viewed from students self-efficacy. The learning model compared were NHT with scientific approach, SNH with scientific approach, and classical with scientific approach. The type of the research was a quasi-experimental research. The populations were all students of Junior High School in Bantul regency. Sampling was done by stratified cluster random sampling. The samples were students of SMPN 1 Pleret, SMPN 2 Sewon, and SMPN 2 Imogiri. The instruments used were mathematics achievement tests and self-efficacy questionnaire. The data was analyzed using unbalanced two-ways Anova. The conclusion were as follows. (1) SNH with scientific approach gives better mathematics achievement than NHT with scientific approach, and both gives better mathematics achievement than classical with scientific approach. (2) Mathematics achievement of students who have high self-efficacy was better than students who have medium and low self-efficacy, and both (medium and low) have the same mathematics achievement. (3) For NHT with scientific approach, students who have high and medium self-efficacy have the same mathematics achievement. Mathematics achievement of students who have high self-efficacy was better than students who have low self-efficacy. Students who have medium and low self-efficacy have the same mathematics achievement. For SNH with scientific approach, mathematics achievement of students who have high self-efficacy was better than students who have medium and low self-efficacy, and both (medium and low) have the same mathematics achievement. For classical with scientific approach, students who have high, medium, and low self-efficacy have the same mathematics achievement. (4) For students who have high self-efficacy, SNH with scientific approach gives better mathematics achievement than NHT with scientific approach and classical with scientific approach. NHT with scientific approach and classical with scientific approach gives the same mathematics achievement. For students who have medium and low self-efficacy, all learning models gives the same mathematics achievement.Keywords: Numbered Heads Together (NHT), Structured Numbered Heads (SNH), classical, scientific approach, self-efficacy.